Optimalisasi Kerja Tabung Induksi Menggunakan Mekanisme Katup pada Mesin Dua Langkah Jenis Yamaha Force 1 ZR - Masy’ari, Masy’ari (Semesta Teknika, 2008)
Rapid development of the automotive world, especially in the two-wheel motor vehicles, must also be compensated with fuel efficiency. Many ways has been used to save fuel for vehicles, particularly for two strokes (2t) gasoline motor, that uses YEIS (Yamaha Energy Induction System) technology, or known as tube Induction. This technology in general is used in Yamaha motorcycle engine with cylinder volume ranging from 155 cc, 135 cc, 150 cc to 250 cc. However the application of YEIS tube is not optimal. The goal of this research is to optimize the performance of the system by creating a system with valve mechanism to regulate incoming and outgoing flow of the mixture of fuel-air into the YEIS system. Induction tube acts as a buffer for fuel-air mixture preventing the mixture from returning to the carburetor during process strokes and then dispose of the rinse proceed with steps, so that the remaining fuel is not futile. The research was started with constructing induction tube, valves and valve housing, assembling and testing. The results of this research indicates that two-wheeled vehicles using an induction tube efficiency has better fuel efficiency than two-wheeled vehicle without induction tube and two-wheeled vehicle equipped with induction tube without the valve mechanism. The result also indicates that the acceleration of the vehicle is not reduced.